Effective mathematics teaching : Research agenda for mathematics education - Grouws, Douglas A.; Jones, Douglas; Cooney, Thomas J. (Reston, Va : National Council of Teachers of Mathematics, 1988)
Addressing fundamental issues in establishing a framework for effective mathematics teaching, the papers provide current research for mathematics instructors and suggestions for future research. Topics discussed include: teaching for higher-order thinking; pedagogical expertise; content determinants; computer usage; cross-cultural studies; and professional and research agendas.
Keywords: Mathematics -- Study and teaching -- Congresses